Should tech giants be broken up to ensure fair competition? - Galib, Ahsan Habib (Riga Graduate School of Law, 2022)
The global financial crisis gave renewed popularity to the concept that some financial institutions are “too big to fail”. A similar argument can be extrapolated to describe the current problem of the exploding power of digital technology companies, collectively known as the “Big Tech”. In competition law, there is a significant level of interest in how these digital technology powerhouses such as Google or Alphabet, Meta, Apple and Amazon establish or assert their market power. This paper analyses the current provisions of the EU competition law and its current ability to meaningfully counteract, or encourage free-market solutions to tech giant dominance. The thesis proposes two solutions for the future - to keep these companies under market control through antitrust (United States) / cartel (European Union) legal action and possible break-up, and the second is the emergence of new market entrants that could challenge the transnational giants' market dominance – allowing for the growth of an innovative and truly competitive, technology sector for a global free-market economy.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law; Big Tech